2017
DOI: 10.1016/j.pan.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and aetiology of acute pancreatitis across Europe

Abstract: The incidence of acute pancreatitis varies across Europe. Gallstone is the dominant aetiology in southern Europe and alcohol in eastern Europe with intermediate ratios in northern and western Europe. Acute pancreatitis continues to increase throughout most of Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
195
6
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(249 citation statements)
references
References 72 publications
9
195
6
11
Order By: Relevance
“…The worldwide incidence of acute pancreatitis is rising, thus further increasing its burden on healthcare services 2. Acute pancreatitis is an inflammatory process which causes a local and systemic inflammatory response syndrome (SIRS).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide incidence of acute pancreatitis is rising, thus further increasing its burden on healthcare services 2. Acute pancreatitis is an inflammatory process which causes a local and systemic inflammatory response syndrome (SIRS).…”
Section: Introductionmentioning
confidence: 99%
“…A known classification of the causes of CP is the TIGARO system: T -toxic-metabolic, I -idiopathic, G -genetic, A -autoimmune, R -recurrent and severe acute pancreatitis, O -obstructive [33]. Alcohol dominates among various causes of both acute and chronic pancreatitis [5][6][7][8]; however, in some patients the aetiology remains unknown [2]. In addition, in 10-25% of patients with CP the risk factors are unclear and are qualified as idiopathic pancreatitis (ICP) [34].…”
Section: Acute and Chronic Pancreatitismentioning
confidence: 99%
“…It was confirmed that pancreatic cancer frequently develops in the group of patients with CP [2][3][4]. Alcohol dominates among the causes of acute, as well as chronic pancreatitis [5][6][7][8]; nevertheless, in some patients the aetiology remains unknown [2,6,9,10]. This proves the existence of other environmental and genetic factors that should be taken into consideration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is one of the leading causes of hospital admission of gastrointestinal origin, with a reported annual incidence ranging from 4.6 to 100 per 100,000 in Europe [1]. Its incidence appears to be rising, with a median increase of 3.4% per year [1], most likely due to the obesity epidemic and its relationship with gallstones.…”
mentioning
confidence: 99%
“…Its incidence appears to be rising, with a median increase of 3.4% per year [1], most likely due to the obesity epidemic and its relationship with gallstones.…”
mentioning
confidence: 99%